Amidation induced self-reduction of p-GO with Lewis-base termination for all-inorganic CsPbIBr2 perovskite solar cells. Issue 45 (28th September 2021) - Du, Jian; Duan, Jialong; Guo, Qiyao; Duan, Yanyan; Yang, Xiya; Zhou, Quanzhu; Tang, Qunwei
Abstract : Fluoroaniline terminated graphene oxide is demonstrated to manipulate the defective interface of perovskite film, finally delivering an efficiency up to 11.08% with superior stability as well as the reduced Pb 2+ leakage. Abstract : Simultaneously tailoring the interfacial energetics and healing the defective nanostructure of perovskite films is important for promoting the power conversion efficiency of perovskite solar cells (PSCs). Herein, a fluoroaniline molecule-terminated graphene oxide (GO) is fabricated as an interface modulator in all-inorganic CsPbIBr2 PSCs. Owing to the amidation reaction induced p–π conjugation effect with an adjacent benzene ring, the spontaneous electron transfer from oxygen-containing groups at the GO surface to the aniline unit causes the self-reduction and p-type doping of GO, benefiting hole extraction and delocalization. Together with the passivation effect by –F termination with under-coordinated Pb 2+, the best device delivers an efficiency of 11.08% with superior stability originating from the presence of hydrophobic C–F bonds, the reduced defects and suppressed ion migration. Moreover, the functionalized GO can effectively capture and obstruct the leakage of Pb 2+ ions from a destructive device, demonstrating its unique advantages in high-performance PSC platforms.